Investigating the risk factors affecting the control of Diabetes and Hypertension in the refugees living in Egypt - Seada, Noura (AUC Knowledge Fountain, 2026)
Introduction: Non-Communicable Diseases (NCDs) account for 74% of global deaths, with high prevalence of Diabetes and Hypertension worldwide. Egypt hosts over 1 million registered refugees and asylum seekers, often lacking inclusion in social protection or insurance schemes. This study aimed to assess the factors affecting the control of Type 2 Diabetes (T2D) and Hypertension (HTN) among Syrian and Sudanese refugees in Egypt, focusing on healthcare access, sociodemographic characteristics, lifestyle, and health behaviours. Methods: This study employed a cross-sectional design using a self-administered questionnaire and BMI measurement. Data were collected from 246 refugees diagnosed with type T2D and/or HTN in the urban settings of Cairo, Giza, and Alexandria, primarily through convenient sampling via refugee-led organisations (RLOs). The survey instrument included standardised tools for measuring diet, lifestyle, social support, and access to care. Statistical analysis included descriptive statistics and multivariate logistic regression model to identify predictors of disease control, which was defined as the absence of disease complications in our sample. Results: The main predictors of disease control after controlling of other sociodemographic factors and access to care variables were gender, duration of displacement, nationality and ability to access care. Males in our sample had higher rate of T2D and higher odds of reporting foot complications (OR = 6.93; 95% CI: 1.43–33.71) compared to females. Sudanese participants were significantly less likely to report renal complications (OR = 0.22; 95% CI: 0.06–0.83), and lower rate of cardiac complications (10.9% vs. 37.8%) compared to Syrians. Multivariate logistic regression has also identified older age ( ≥ 50 years) as the most robust predictor of cardiac complications ((OR = 6.30; 95% CI: 1.71–23.18).. Living in Egypt for four years or longer was found to be associated with increased odds of cardiac complications (OR = 3.99; 95% CI: 1.07-14.94). Conversely, reporting the ability to access care had a protective effect on reporting diabetic foot complications (OR = 0.19; 95% CI: 0.04–0.90). The main barrier to accessing necessary care was the unaffordability of services (51.5%) and was also the main reported reason for noncompliance on medications. Conclusion: Sociodemographic factors, particularly Gender, age and prolonged length of stay, were some of the main drivers of serious NCD complications (cardiac and renal events) in this urban refugee population. Access to care was a reliable protective factor against developing the complications of the disease. Financial barriers constitute the main reported obstacle to care access. Therefore, there is a pressing need for sustainable health financing models that integrate refugees into national health schemes.